Solutions for Young Entrepreneurs in the Socially-Based Fourth Industrial Revolution Era - Jumali, Muhamad Abdul; Diego Dzikrul Sabbiqun; Rusdiyantoro (Tibuana, 2024)
A startup is a venture or business within a social organization that leverages information technology to conduct its business, targeting a wide market audience and establishing numerous relationships to support its operations. A digital startup is a business within an organization that primarily operates its business through computers and is managed by various partners handling aspects of marketing, sales, and payments. Essentially, this digital startup serves as an intermediary for marketing or ongoing business activities. The strategy of a digital startup revolves around maximizing marketing efforts through technology, staying updated with current trends, and maintaining courteous and measured communication to provide comprehensive and inseparable customer service, using this approach to fulfill their needs. Social entrepreneurship during the era of the Fourth Industrial Revolution involves combining creativity with rapidly advancing technology for sociallybased entrepreneurial activities.